Delivering Secure CEU Training Utilizing Zoom - Brett W. Bultemeier; Michelle Atkinson (EDIS)
Delivering online, live CEU (Continuing Education Unit) training has become increasingly practical with the development of programs like Zoom. However, there are key differences between the two platforms that Zoom offers, Zoom Meeting and Zoom Webinar. Understanding the pros and cons of each platform and how to utilize each to deliver CEU content is key. Through descriptions and screenshots of the program, this new 7-page publication of the UF/IFAS Pesticide Information Office helps readers navigate the platforms and better understand which one best fits their needs. Written by Brett W. Bultemeier and Michelle Atkinson. https://edis.ifas.ufl.edu/pi286